Functional surgery for pain - Teixeira, Manoel Jacobsen; Haman, Clement; Teixeira, William Gemio Jacobsen (Revista de Medicina, 2001)
Many functional neurocirurgical procedures are useful in patients with muscleskeletal pains. The surgical descompression of roots or nerve trunks are indicated in cases of stenosis of the pathways of these structures due to inflammatory, degenerative or oncologic lesions fractures or bone deformities or oncologic lesions. Sympatectomies are not very effective in cases of tipe II complex regional pain syndromes; facet rhyzotomies are efficient in cases of cervicalgia, dorsalgia and lombalgia due to myofascial pain syndromes, thermal disc nucleolysis are efficient in cases of lombalgia due to discal pains; DREZ is usefful in the treatment of neuropathic pain and spasticity; esencephalotomies, thalamotomies and psychosurgeries are efficient in difficult cases. Endocrinological ablative procedures including hypophisectomies are efficient in cases of bone pains resulting from secondaries of prostate, breast and endometrium. Except for post-laminectomy or neuropatic pain, the stimulation of the central nervous stystem is not appropriate for the treatment of muscleskeletal pain. The infusion of morphine is a very effective method for the treatment of the majority of muscle skeletal conditions.